Transferred melanoma-specific CD8+ T cells persist, mediate tumor regression, and acquire central memory phenotype - Chapuis, Aude G; Thompson, John A; Margolin, Kim A; Rodmyre, Rebecca; Lai, Ivy P; Dowdy, Kaye; Farrar, Erik A; Bhatia, Shailender; Sabath, Daniel E; Cao, Jianhong; Li, Yongqing; Yee, Cassian (Proceedings of the National Academy of Sciences - PNAS, 2012)
Adoptively transferred tumor-specific T cells offer the potential for non-cross-resistant therapy and long-term immunoprotection. Strategies to enhance in vivo persistence of transferred T cells can lead to improved antitumor efficacy. However, the extrinsic (patient conditioning) and intrinsic (effector cell) factors contributing to long-term in vivo persistence are not well-defined. As a means to enhance persistence of infused T cells in vivo and limit toxicity, 11 patients with refractory, progressive metastatic melanoma received cyclophosphamide alone as conditioning before the infusion of peripheral blood mononuclear cell-derived, antigen-specific, CD8(+) cytotoxic T-lymphocyte (CTL) clones followed by low-dose or high-dose IL-2. No life-threatening toxicities occurred with low-dose IL-2. Five of 10 evaluable patients had stable disease at 8 wk, and 1 of 11 had a complete remission that continued for longer than 3 y. On-target autoimmune events with the early appearance of skin rashes were observed in patients with stable disease or complete remission at 4 wk or longer. In vivo tracking revealed that the conditioning regimen provided a favorable milieu that enabled CTL proliferation early after transfer and localization to nonvascular compartments, such as skin and lymph nodes. CTL clones, on infusion, were characterized by an effector memory phenotype, and CTL that persisted long term acquired phenotypic and/or functional qualities of central memory type CTLs in vivo. The use of a T-cell product composed of a clonal population of antigen-specific CTLs afforded the opportunity to demonstrate phenotypic and/or functional conversion to a central memory type with the potential for sustained clinical benefit.